MENUMBUHKAN MINAT BACA PADA ANAK USIA 5-6 TAHUN MELALUI CERITA BERGAMBAR DI KB NURUL MA’RIFAH KALISAT KABUPATEN JEMBER - Sarifatul Lailika; Mahendra Aswit Sandra Barata; Nury Kurnia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to foster reading interest in children aged 5-6 years through the use of picture stories at the Nurul Ma'rifah Kalisat Kindergarten, Jember Regency. The problem faced is the low interest in reading in children, which is evident from their greater interest in digital games compared to reading books. This indicates an urgent need to create a supportive and engaging environment for children to read. The general objective of this study is to increase reading interest in early childhood. While the specific objectives include: (1) identifying factors that hinder children's reading interest, (2) implementing interesting learning methods through picture stories, and (3) evaluating the increase in children's reading interest after the implementation of the method. The research method used is Classroom Action Research (CAR) with the Kemmis and McTaggart model, which consists of four stages: planning, action implementation, observation, and reflection. This research will be conducted in two cycles, with 15 children selected purposively as research subjects. The expected output of this study is an increase in children's reading interest, which can be measured through children's participation in reading activities, responses to stories, and their ability to retell the story content. It is hoped that the results of this study can contribute to the development of a more effective and relevant PAUD curriculum to children's needs, as well as improve the quality of early childhood education in the digital era.